The PHO84 gene of Saccharomyces cerevisiae encodes an inorganic phosphate transporter. - Bun-Ya, M (1991)
The PHO84 gene specifies Pi-transport in Saccharomyces cerevisiae. A DNA fragment bearing the PHO84 gene was cloned by its ability to complement constitutive synthesis of repressible acid phosphatase of pho84 mutant cells. Its nucleotide sequence predicted a protein of 596 amino acids with a sequence homologous to that of a superfamily of sugar transporters. Hydropathy analysis suggested that the secondary structure of the PHO84 protein consists of two blocks of six transmembrane domains separated by 74 amino acid residues. The cloned PH084 DNA restored the Pi transport activity of pho84 mutant cells. The PHO84 transcription was regulated by Pi like those of the PHO5, PHO8, and PHO81 genes. A PHO84-lacZ fusion gene produced beta-galactosidase activity under the regulation of Pi, and the activity was suggested to be bound to a membrane fraction. Gene disruption of PHO84 was not lethal. By comparison of nucleotide sequences and by tetrad analysis with GAL80 as a standard, the PHO84 locus was mapped at a site beside the TUB3 locus on the left arm of chromosome XIII.